ACCESSIBILITY FOR DIFABLED ON PUBLIC SPACE IN SIMPANG LIMA SEMARANG, INDONESIA - Kurniati, Rina; Almas, Dhafina (Science and Technology Research Centre, Universitas PGRI Semarang, 2020)
Simpang Lima is a CBD of Semarang City that has a high level of activity. Improvements have been made to the faces of the Simpang Lima area and included the provision of facilities for difabled, but not yet many difabled persons accessing the area due to difficult access to and from the area. This research aims to assess the accessibility of difable to public open space in Simpang Lima area by analyzing the application of public facilities, especially for difabled and analyzing alternative solutions in the provision of accessible public facilities based on difabled needs. The Data acquired by distributing questioner to the difabled who are members of the